Implementation of character education for vocational high school internship students at Subandi Giyanto Studio - Lestari, Anggita Mundhi; Astuti, Eni Puji (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
The research aims to describe character education through internships at Subandi Giyanto Studio for vocational students. Character education is implemented through habituation and exemplary. This research uses qualitative research with a descriptive case study method"”data collection techniques using observation techniques, interviews, documentation, and field notes. The research subjects were apprentice students conducting data validity by source and technique triangulation. The results of this study indicate that 1) there are five central character education values, namely religious, disciplined, creative, polite, and responsible; 2) the activities are integrated into the apprenticeship learning process 3) have a good impact on student behaviour and character 4) the obstacles that encountered comes from the emergence of feelings of nervousness, limited communication between students, and the character of students who are heavily influenced by technology, 5) efforts made to overcome obstacles during the process of implementing character education include taking a personal approach to students, training apprentice students' sensitivity to the environment, establishing relationships between students, and train student communication.